Three-dimensional cone beam computed tomography analysis protocols for condylar remodelling following orthognathic surgery: a systematic review. Issue 2 (February 2020) - Verhelst, P.J.; Verstraete, L.; Shaheen, E.; Shujaat, S.; Darche, V.; Jacobs, R.; Swennen, G.; Politis, C.
Abstract: Orthognathic surgery involving the mandible can lead to remodelling of the temporomandibular joint (TMJ). Cone beam computed tomography (CBCT) provides an easily accessible three-dimensional (3D) approach to study this entity. A systematic review of the literature was performed with the aim of identifying condylar remodelling analysis protocols using CBCT-derived 3D models. The search yielded 10 eligible studies. The systematic review identified three pillars of a condylar remodelling analysis protocol that were retrievable from each of the included studies: (1) registration, (2) segmentation, and (3) analysis. The studies lacked consensus on how these pillars should be transferred to their respective protocol. Through critical assessment, criteria for a universal condylar remodelling analysis are suggested: (1) performance of a regional voxel-based registration of baseline and postoperative CBCT scans using an anatomical region not prone to postoperative changes, (2) application of a (semi-)automated 3D segmentation algorithm, (3) performance of a combination of both volumetric and surface-based 3D condylar analysis, and (4) extensive validation of each step of the protocol. The homogenization of condylar remodelling analysis protocols and their incorporation into virtual planning software suites raises the potential for the inclusion of larger numbers of patients in future prospective studies in order to gain evidence-based data.